1987
DOI: 10.1172/jci112916
|View full text |Cite
|
Sign up to set email alerts
|

Transketolase abnormality in cultured fibroblasts from familial chronic alcoholic men and their male offspring.

Abstract: We have investigated a thiamine-dependent enzyme, transketolase, in cultured fibroblasts from 41 human subjects, including patients with alcoholism-associated Wernicke-Korsakoff syndrome (n = 3), familial chronic alcoholic males (a = 7), their sons (n = 7), nonalcoholic men (n = 7), their male offspring (a = 7), and three generations of an Amish family (n = 10)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 19 publications
0
24
0
1
Order By: Relevance
“…The authors suggested that the patients were genetically predisposed to this disorder. Their results were later supported by Mukherjee et al [107] although the observed di erence between the apparent cofactor binding constants for patients and controls was much smaller. In this laboratory TK isolated from erythrocytes of WK syndrome patients and controls did not display any variation in ThDP a nity [113].…”
Section: Variant Forms Of Tkmentioning
confidence: 69%
“…The authors suggested that the patients were genetically predisposed to this disorder. Their results were later supported by Mukherjee et al [107] although the observed di erence between the apparent cofactor binding constants for patients and controls was much smaller. In this laboratory TK isolated from erythrocytes of WK syndrome patients and controls did not display any variation in ThDP a nity [113].…”
Section: Variant Forms Of Tkmentioning
confidence: 69%
“…TKT catalyzes several reactions within the nonoxidative branch of the PP pathway, and together with transaldolase serves as a reversible link between the PP and glycolytic pathways, allowing the cell to adapt to a variety of metabolic needs under changing environmental conditions. TKT is often used to assess thiamine status in man (18), and alterations in TKT chemicophysical or kinetic properties have been implicated in a variety of pathological conditions including Wernicke-Korsakoff's Syndrome (19,20), Alzheimer's disease (21,22), fibromyalgia (23), severe malnutrition (24,25), and alcoholism (26).…”
mentioning
confidence: 99%
“…In the other patients WE appears to be an uncommon complication of common medical conditions (such as hyperemesis of pregnancy, hemodialysis and banded gastroplasy), a fact which also suggests that the development of the disorder depends on a predisposition which may be genetic. It was suggested that altered transketolase activity may predispose patients to alcohol-associated WE [13, 14]but sequencing of the enzyme’s coding region failed to demonstrate a specific variation which may account for an altered enzyme activity [15]. Future advances in the biochemistry and genetics of thiamine-dependent enzymes may define the precise abnormality and set guidelines for appropriate replacement therapy in such patients.…”
Section: Discussionmentioning
confidence: 99%